Atomic-scale dents on cellulose nanofibers: the origin of diverse defects in sustainable fibrillar materials. Issue 10 (30th August 2022) - Ito, Tomoki; Daicho, Kazuho; Fujisawa, Shuji; Saito, Tsuguyuki; Kobayashi, Kayoko
Abstract : Atomic-scale dent structures on the surfaces of cellulose nanofibers were detected. These dent parts constituted at least 30–40% of the total length of the dispersed nanofibers, and deep dents induced the kinking and fragmentation of nanofibers. Abstract : Atomic-scale dent structures on the surfaces of cellulose nanofibers were detected by comparing the experimentally measured and computer-simulated widths of single nanofibers. These dent parts constituted at least 30–40% of the total length of the dispersed nanofibers, and deep dents induced the kinking and fragmentation of nanofibers.